Case report: A panorama gene profile of ovarian cancer metastasized to axillary lymph node - Yu Xia; Yu Huang; Zheng Liu; Siyuan Song; Yi Wang; Yi Wang; Jing Luo (Frontiers in Immunology)
BackgroundOvarian cancer is among the most lethal gynecologic malignancies, with a high proportion of patients diagnosed at advanced stages, leading to poor survival outcomes. Axillary lymph node metastasis from ovarian cancer is extremely rare and the mechanism is still unclear.MethodsA comprehensive set of clinical and gynecologic oncology assessments were performed, including ultrasound, mammography, MRI, transvaginal ultrasound, and tissue staining. To unravel the carcinogenesis, the next-generation sequencing (NGS) was performed.ResultsConventional examinations and imaging suggested the presence of both occult breast cancer and ovarian cancer. However, immunohistochemical staining confirmed the diagnosis of high-grade serous ovarian carcinoma. Further analysis of NGS identified two novel missense mutations, D326E in BTK (Bruton’s tyrosine kinase) at SH2 domain and D251E in EPHA5 (EPH receptor A5), along with other known cancer- associated mutations. These mutations, particularly the novel missense mutations, may lead to metastasis to the axillary lymph nodes and drug resistance. Therefore, based on these findings, the chemotherapy regimen was adjusted accordingly.ConclusionThis is the first report on the panorama gene profile of ovarian cancer metastasis to axillary lymph node and we found two novel mutations (BTK pD326E and EPHA5 pD251E). This study unraveled the potential mechanism of genetic mutation for tumor metabolism, drug resistance, and metastasis.